Level of self-esteem: Is there any difference among physical, verbal, anti-social, and cyber bullies? - Siti Jaizah Nakman; Nurulwahida Azid; Abdul Hamid Busthami Nur (Institute of Advanced Engineering and Science, 2023)
Bullying is one of the major issues worldwide and is one of the most prevalent school violence. Bullying is a negative behavior toward an individual or group of individuals that are considered weak. Bullying is often associated with self-esteem. Therefore, this study was conducted to identify the influence of students’ tendency to be bullies (physical, verbal, anti-social, and cyber) on self-esteem. This study involved 150 secondary school students in the north of peninsular Malaysia. The study also used the cross-sectional survey method by distributing a set of questionnaires to the respondents. The findings of the study found that students who tend to be bullies for the four categories of bullying, namely physical bullying (ß=0.076, t=3.048, p<0.05), verbal (ß=0.080, t=3.052, p<0.05), anti-social (ß=0.084, t=3.055, p <0.05) and cyber (ß=0.046, t=2.815, p<0.05) had a significant influence on level of self-esteem.